Personnel economics: Strengths, weaknesses and its place in human resource management - Alexander Dilger (Management Revue, 2011)
Personnel economics is a rather young academic (sub-)discipline that applies (micro) economic methodology and insights to the personnel function of companies. It is scientifically fertile and complementary to other disciplinary approaches to personnel issues. Instead of that, an approach without a grounding discipline seems dubious and a self-contained personnel science does not exist.
Keywords: A12; B40; J00; M10; M12; M20; M50; 650; discipline; economics; HRM; human resource management; labour economics; personnel economics